Approaches to teach law in English - Gulmira Juraboyeva Sherali qizi; Rustamova Nazokat Abdullayevna (International Journal on Orange Technologies, 2021)
This article is about teaching law in English by using different approaches. In the below there are some ways to organizing effective classes and solutions which are both students and teachers come across in this field